Advanced remediation of pyrene contaminated soil by double dielectric barrier discharge (DDBD) plasma and subsequent composting process. (September 2022) - Abbas, Yawar; Ajmal, Muhammad; Mustafa, Muhammad Farooq; Stegmann, Rainer; Shao, Yuchao; Lu, Wenjing
Abstract: Due to increasing industrialization, soils are increasingly contaminated by polycyclic aromatics such as pyrene and need gentle treatment to keep the soil functioning. This study applied a double dielectric barrier discharge (DDBD) plasma reactor and composting reactor to remediate pyrene-contaminated soil. The effect of peak-to-peak applied voltages on the remediation efficiency of pyrene was investigated. The experimental results illustrate that pyrene remediation efficiency increased from 43% to 85% when the peak-to-peak applied voltage was increased from 28.0 to 35.8 kV. When using the combined method of DDBD and composting, 90–99% of pyrene could be removed, while a reduction of 76.5% was achieved using only composting, indicating the superiority of the combined system. Moreover, the authors could demonstrate that DDBD plasma treatment improves humification in the post-composting process as humic acid (HA) concentrations increased to 7.7 mg/g with an applied voltage of 35.8 kV; when composting was used as the sole treatment method, only 3.4 mg/g HA were produced. The microbial activity in the DDBD plasma-treated soil peaked on the 5th day and had a 2nd rise afterwards. The authors demonstrate that the combined technology of DDBD plasma and composting is a promising method for soil remediation with persistent organic pollutants. This treatment approach improves pollutant degradation efficiency and facilitates further humification, potentially restoring the function of contaminated soil. This approach could be considered a cost-effective and green strategy for soil remediation with persistent organic pollutants. Graphical abstract: Image 1 Highlights: Bioremediation of Pyrene contaminated soil under influence of NTP. Composting combined with DDBD plasma pretreatment showed higher pyrene removal efficiency than composting alone. Higher voltage of DDBD plasma reactor enhanced pyrene remediation. Combined process was also superior in humification and microbial activity.